Kennisoverdracht rond cacao in de Atlantische zone van Costa Rica - Groot, A.A. de. (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), Turrialba (Costa Rica). Atlantic Zone Programme Agricultural University Wageningen, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
11 tab. 16 ref. Sum. (Nl)